Identifying solid luminogens through gold-catalysed intramolecular hydroarylation of alkynes - Shaikh, Aslam C.; Shalini, S.; Vaidhyanathan, Ramanathan; Mane, Manoj V.; Barui, Ayan Kumar; Patra, Chitta Ranjan; Venkatesh, Yeduru; Bangal, Prakriti Ranjan; Patil, Nitin T. (European Journal of Organic Chemistry, 2015)
The identification of a new class of luminogens based on pyrrolo-quinoxaline embedded coumarin (PQC) structures is reported. The reaction relies on the gold-catalyzed hydroarylation reaction of appropriately substituted aryl alkynoates that produces molecules that exhibit solvatochromism and aggregation-induced emission enhancement (AIEE) phenomena. The application of PQCs for live cell imaging has also been demonstrated.
Keywords: Cell imaging; Dyes/pigments; fluorescence; Gold; Luminescence; Solvatochromism

Ionic pyridinium-oxazole dyads: design, synthesis, and application in mitochondrial imaging - Shaikh, Aslam C.; Varma, Mokshada E.; Mule, Ravindra D.; Banerjee, Somsuvra; Kulkarni, Prasad P.; Patil, Nitin T. (Journal of Organic Chemistry, 2019)
We recently developed an oxidative intramolecular 1,2-amino-oxygenation reaction, combining gold(I)/gold(III) catalysis, for accessing structurally unique ionic pyridinium-oxazole dyads (PODs) with tunable emission wavelengths. On further investigation, these fluorophores turned out to be potential biomarkers; in particular, the one containing -NMe2 functionality (NMe2-POD) was highly selective for mitochondrial imaging. Of note, because of mitochondria's involvement in early-stage apoptosis and degenerative conditions, tracking the dynamics of mitochondrial morphology with such imaging technology has attracted much interest. Along this line, we wanted to build a library of such PODs which are potential mitochondria trackers. However, Au/Selecfluor, our first-generation catalyst system, suffers from undesired fluorination of electronically rich PODs resulting in an inseparable mixture (1:1) of the PODs and their fluorinated derivatives. In our attempt to search for a better alternative to circumvent this issue, we developed a second-generation approach for the synthesis of PODs by employing Cu(II)/PhI(OAC)(2)-mediated oxidative 1,2-amino-oxygenation of alkynes. Thes newly synthesized PODs exhibit tunable emissions as well as excellent quantum efficiency up to 0.96. Further, this powerful process gives rapid access to a library of NMe2-PODs which are potential mitochondrial imaging agents. Out of the library, the randomly chosen POD-3g was studied for cell-imaging experiments which showed high mitochondrial specificity, superior photostability, and appreciable tolerance to microenvironment changes with respect to commercially available MitoTracker green.